Is Dhaka Stock Exchange (DSE) Efficient? A Comparison of Efficiency Before and After the Market Crisis of 2010 - Maxim, Maruf Rahman; Miti, Tasfia Awal; Arifuzzaman, S. M (Asian Business Review, 2013)
This paper tests for the weak form of efficiency in DSE. A major objective of this paper is to compare and analyse the efficiency of the market before and after the market crash of December, 2010. The sample includes DSEGEN price index daily closing values. The data is divided among two time periods, year 2009-2010 is used to test the efficiency before the market crash and 2011-2012 is used to test the efficiency after the market crash. Kolmogorov-Smirnov and the Shaprio-Wilk tests are used to test the normality of returns and for both the time periods, the returns distributions are non normal. Runs test is used to test for the randomness of returns. The result of runs test is quite interesting. It shows that returns were not random before the market crash. Numerous other previous researches also show non randomness of returns in DSE. But surprisingly random walk is observed for the returns after the market crash. It requires further studies to understand such abnormality. JEL Classification Code: L11, H12